Survey of Physical Fitness Level of Class XI Mia Students at SMA Negeri 21 Surabaya - Firmansyah Prawironastro, Muhammad Bagas; Ridwan, Mochamad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research is based on student activities both in the school environment and activities outside of school which are felt to have an influence on the level of physical fitness, then the aim of carrying out this research is to find out the description of the physical fitness level of class XI MIA students at SMA Negeri 21 Surabaya. This research is included in non-experimental research, namely in this research the results of external validity are more emphasized with the aim of providing real data results without any manipulation or intervention from various parties to the samples studied. This research uses a quantitative descriptive approach with a survey method for collecting data in research. The instrument used in this research was the MFT test or Multistage Fitness Test. The data analysis technique used is a descriptive test which includes mean, standard deviation and percentage. After carrying out research on class XI MIA students at SMA Negeri 21 Surabaya, the results showed that the physical fitness level of class The average MFT results show a low value, with the highest average in class XI MIA 4 at 29.81 and the lowest average in class XI MIA 3 at 22.54. The percentage of students in the very poor category with class XI MIA 1 reaching 100% at the very low level, class XI MIA 3 reaching 88.23%, class . Meanwhile, the sufficient category was only found in a few students in class XI MIA 3.